Knowledge and Preparedness of Earthquake among Management Graduates in Kathmandu District of Nepal - Pokharel, Yagya Raj (Nepal Journal of Multidisciplinary Research, 2022)
Introduction: Earthquakes are one of the most deadly and unexpected natural disasters, resulting in thousands of lives and huge economic loss. Nepal is a country that experiences earthquakes on a regular basis. Previous study has shown that increasing public awareness and preparedness for future earthquakes is crucial for minimizing the number of deaths caused and property loss. To reduce the damage caused by such earthquakes, it is vital to analyze people's understanding and readiness. Purpose: The main aim of the study is to identify the Knowledge and Preparedness of Earthquake and the different between knowledge of earthquake and preparedness of earthquake among graduates in Kathmandu district of Nepal. Design/methodology/approach: The research was carried out using a descriptive design. The research involved 144 management faculty students at the bachelor's and master's level. The core data was collected via an online KoBoToolbox form. The data was analyzed using the mean and paired sample t-test. The Cronbach's Alpha value was used to assess the data's reliability. Findings: Students are well knowledgeable in earthquakes, including how to prepare and what to do in case of an earthquake. Yet, their preparations are inadequate in comparison to their knowledge. There was a significant difference between preparedness (M=3.5357, SD=0.489) and knowledge (M=3.8194, SD=0.4548), because p=0.000 which is less than .05 significant level. Originality/value: The study found that management students have a good understanding of earthquakes, but they are not well prepared for the earthquake.